2017
DOI: 10.1080/08941920.2017.1347974
|View full text |Cite
|
Sign up to set email alerts
|

Human–Wildlife Conflicts and their Associated Livelihood Impacts in and Around Chebera-Churchura National Park, Ethiopia

Abstract: Human-wildlife conflict is one of the major challenges in conservation biology. Here, we investigated the human-wildlife conflicts and their impacts in and around Chebera-Churchura National Park (CCNP), Ethiopia. We conducted semi-structured interview for 300 people and five focus group discussions from November 2010 through January 2011. Additionally, scats of sixty spotted hyenas were collected and analyzed. Totally, 12 carnivores, 6 herbivores and 2 primate species posing a significant problem were identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 31 publications
3
24
1
Order By: Relevance
“…Higher degree of conflict with wildlife (90%), due to crop damage and livestock predation, was recorded in this study, which is in agreement with previous studies in different conservation areas of the country (Tessema et al 2010;Kumessa and Bekele 2013;Yosef 2015;Acha and Temesgen 2015). As indicated by Anthony (2007) and Shibia (2010), crop and livestock losses due to wildlife have resulted in the development of negative attitude by local communities towards Kruger National Park in South Africa and Marsabit National Reserve Kenya, respectively.…”
Section: Perception and Attitude Towards Livestock-wildlife Interactionssupporting
confidence: 80%
See 1 more Smart Citation
“…Higher degree of conflict with wildlife (90%), due to crop damage and livestock predation, was recorded in this study, which is in agreement with previous studies in different conservation areas of the country (Tessema et al 2010;Kumessa and Bekele 2013;Yosef 2015;Acha and Temesgen 2015). As indicated by Anthony (2007) and Shibia (2010), crop and livestock losses due to wildlife have resulted in the development of negative attitude by local communities towards Kruger National Park in South Africa and Marsabit National Reserve Kenya, respectively.…”
Section: Perception and Attitude Towards Livestock-wildlife Interactionssupporting
confidence: 80%
“…Most studies on perceptions and attitudes about livestock-wildlife interface areas give more emphasis to wildlife conservation goals and strategies (Decker et al 2001;Kumessa and Bekele 2014;Acha and Temesgen 2015) than the challenges of livestock-wildlife interactions on local livestock producers bordering protected areas. However, studying the challenges in the livestockwildlife interface will address main concerns of the pastoral production systems and at the same time major problems of wildlife management in the area, which helps to design management tools that mitigate problems of both the livestock and the wildlife sector.…”
Section: Introductionmentioning
confidence: 99%
“…The impacts of wildlife to the local community can be in terms of damage to crops, livestock predation, injuries to human beings, and losses of human lives (Haule et al 2002;). Several studies reported injuries to human beings and even death due to wild animal attacks (Haule et al 2002;Acha and Temesgen 2015). It also involves the lack of access to wildlife resources for religious and cultural purposes (Springer 2009), restriction on the use of the resources (Beltrán and Phillips 2000), conflicts from enforcement activities (Springer, 2009) and displacement and resettlement (Coad et al 2008).…”
Section: Costs Wildlife Conservation Imposes To Local Peoplementioning
confidence: 99%
“…Humanwildlife conflicts pose from minor to serious problems to the local community. Major impacts of such interaction are the loss of primary food, cash crops, and livestock (Acha and Temesgen, 2015;Berihun et al 2016;Gobosho et al 2016). However, human injuries and death due to direct Journal of Resources Development and Management www.iiste.org ISSN 2422-8397 An International Peer-reviewed Journal Vol.61, 2019 20 attack, social costs from disturbing sleeping time, and children schooling for guarding such problematic animals are another local consequence of humanwildlife conflicts in rural areas of developing countries (Adams and Hutton, 2007;Bajracharya et al 2007;FAO, 2009).…”
Section: Humanwildlife Conflictsmentioning
confidence: 99%
See 1 more Smart Citation